Enhancing Elementary Students' Learning Interest Through Teams Games Tournament with Monopoly Media : A Quasi-Experimental Study in Science and Social studies - Azzahra Nabilla Atmajanti; Abdul Rahman; Sinta Satria Dewi Pendit; Azizah Azizah; Danti Indriastuti Purnamasari (Papanda Publisher, 2026)
This quasi-experimental study examined the effect of the Teams Games Tournament (TGT) learning model supported by monopoly learning media on fourth-grade students' learning interest in IPAS (Science and Social studies) subjects. Forty-four students at MI Muhammadiyah Al-Haq Palu were purposively selected based on low learning interest indicators and randomly assigned to experimental (n=22) and control (n=22) groups. The experimental group received TGT instruction with monopoly games, while the control group experienced conventional lecture-based teaching. A validated 20-item Guttman scale questionnaire measured learning interest before and after the two-session intervention. Data analysis employed paired samples t-tests, independent samples t-tests, normalized gain calculations, and Cohen's d effect size. Results revealed significant learning interest improvements in both groups (p < 0.001), with the experimental group demonstrating substantially greater gains (mean increase = 1.36, N-gain = 0.37) compared to the control group (mean increase = 0.91, N-gain = 0.18). The independent samples t-test confirmed significant differences between groups (p < 0.001, t = 3.954), with a large effect size (Cohen's d = 0.82). These findings indicate that TGT supported by monopoly media significantly and practically enhances elementary students' learning interest, offering educators an accessible, evidence-based strategy for improving affective outcomes in integrated science education.